Optimization of composition and characteristics of economically alloyed cast iron for mold tubes - R. E. Trubitskij; A. G. Slutskij; B. A. Kaledin (Литьë и металлургия, 2003)
With the help of the methods of mathematical planning of the experiment there are conducted the tests on optimization of the composition and characteristics of the economically alloyed cast iron for muffs. There is studied the influence of alloying elements Си, Ni, Cr, V, В, Mg, Ti on the muffs solidity. There are received the mathematical adequate equations, which allowed to optimize the cast composition and solidity. On the basis of these results there are worked out the technology of muffs production and approved at LLMZ.